Salvation of a saint - Higashino, Keigo, 1958- (Higashino, Keigo, 1958- Detective Galileo novels, 2012)
When a man about to leave his wife is found murdered and the wife has a too-convenient alibi that convinces a smitten lead detective of her innocence, Professor Manubu Yukawa is tapped by a concerned Kaoru Utsumi to solve a seemingly impossible case.